2015
DOI: 10.3402/fnr.v59.27830
|View full text |Cite
|
Sign up to set email alerts
|

The influences of purple sweet potato anthocyanin on the growth characteristics of human retinal pigment epithelial cells

Abstract: BackgroundAnthocyanins have been proven to be beneficial to the eyes. However, information is scarce about the effects of purple sweet potato (Ipomoea batatas, L.) anthocyanin (PSPA), a class of anthocyanins derived from purple sweet potato roots, on visual health.ObjectiveThe aim of this study was to investigate whether PSPA could have influences on the growth characteristics (cellular morphology, survival, and proliferation) of human retinal pigment epithelial (RPE) cells, which perform essential functions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The most abundant ACN in the edible parts of plants is cyanidin‐3‐glucoside (C3G) . C3G facilitates rhodopsin regeneration in rod photoreceptors, interacts directly with the dark and light forms of rhodopsin and opsin protein, and inhibits the photooxidation of retinal pigment epithelial (RPE) cells . In addition, C3G can be detected in the eyes by oral administration of blueberry, thereby suggesting its possible role in protecting against retinal diseases .…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant ACN in the edible parts of plants is cyanidin‐3‐glucoside (C3G) . C3G facilitates rhodopsin regeneration in rod photoreceptors, interacts directly with the dark and light forms of rhodopsin and opsin protein, and inhibits the photooxidation of retinal pigment epithelial (RPE) cells . In addition, C3G can be detected in the eyes by oral administration of blueberry, thereby suggesting its possible role in protecting against retinal diseases .…”
Section: Introductionmentioning
confidence: 99%
“…However, food and fodder dual-purpose cultivars were not available in African sweetpotato germplasm (Niyireba et al, 2013) until the recent release of RW cultivars by the Rwanda Agriculture Board and the International Potato Center (CIP) (Shumbusha et al, 2014). Purplefleshed sweetpotatoes (PFSP) are the sources of antioxidants (Teow et al, 2007), and anthocyanins derived from PFSP affect the growth of human retinal pigment damageprotective activities on epithelial cells (Kubow et al, 2016;Sun et al, 2015). Moreover, PFSP can be used for natural food coloring, which is a relatively new market for sweetpotato and cultivars high in anthocyanin, are increasingly becoming popular in Asia used fresh or in a variety of processed snacks (Gilbert, 2005;Timberlake and Henry, 1988).…”
mentioning
confidence: 99%
“…By contrast, PSPA exhibited an opposite effect in non-cancerous cells by enhancing cell viability and resistance to apoptosis. Furthermore, according to previous studies, PSPA was capable of inhibiting the proliferation in multiple cell types ( 24 ), while the proliferation and anti-apoptotic effect of PSPA has also been reported ( 25 , 26 ). The reason for this appeared contradictory effect was not very clear.…”
Section: Discussionmentioning
confidence: 75%
“…This was in agreement with some cancer cell studies ( 13 , 14 ). There were studies that reported a promotion effect of PSPA on cell viability ( 25 , 33 ). The anthocyanins appeared to have a paradoxical role in the generation of the ROS ( 34 36 ).…”
Section: Discussionmentioning
confidence: 99%